Institutional Ownership and Social Responsibility Disclosure: Evidence from Mining and Energy Companies - Gea Ovelliany Tiaspupa; Barnabas Tridig Silaban (Owner : Riset dan Jurnal Akuntansi, 2025)
This investigation aims to verify the effect of institutional ownership on social responsibility disclosure (SRD) based on Global Reporting Initiative (GRI) standards, with two control variables: financial leverage (FL) and profitability (PROF). The population consists of 50 mining and energy corporations in the Indonesian Capital Market from 2017 to 2022. Moreover, this investigation employs the Slovin formula to grab 33 representative companies from the total population, which are chosen randomly. A regression model is then used to analyze the secondary data. As a result, this investigation reveals a positive association between institutional ownership and SRD. Similarly, this propensity is obtainable when examining the effect of two control variables, FL and PROF, on SRD. Ultimately, this research offers practical examples for these companies to take responsibility for the environment and the surrounding society at their locations.